O direito fundamental ao trabalho e as dificuldades de inclusão da pessoa com deficiência no âmbito das empresas privadas de Belém - PINHEIRO, Francilei Maria Contente (Universidade Federal do Pará, 2017)
The present work has the purpose to treat the right to work and the difficulties of inclusion of people with disabilities in the private companies in the city of Belém. The goal to achieve is to check the reason there is still a large contingent of people with disabilities who are outside the labor market, despite the art. 93, of law 8213, of July 24, 1991 and art. 36 of the Decree 3298, of December 20, 1999, oblige companies with over 100 employees to hire people with disabilities in the percentage 2-5%, it is necessary to know the problems that prevent the occupancy of vacancies to solve them, and promote this way, a more effective and complete inclusion. Regarding the methodological procedure, it is proposed to conduct a qualitative approach, from the execution of documentation and literature research; as well as field research, because of the required production data from questionnaires completed by 60 people with disabilities and 21 companies subject to the quota law. The research field of empirical research is the city of Belém. At the end of the work, identifies the main difficulties and possible solutions to improve the inflow of people with disabilities in the labor market. We conclude that quotas have been of great importance in the inclusion of people with disabilities, but it is necessary that companies, society and public authorities act together to promote a number of changes to ensure the right to work in a broad and dignified manner to the disabled person, because the greatest difficulties are not the disability itself.